Community Empowerment as a Strategy for Sustainable Livelihood Development: A Case Study of Lung Anai Village - Aprylasari, Dede; Agung Enggal Nugroho; Mohamad Fadli; Erwin Arief Rochyat; Putri Daulika; Ke-Chung Peng (LOSARI DIGITAL, 2026)
Lung Anai Village, located in the mining buffer zone of Kutai Kartanegara Regency, experiences complex livelihood dynamics due to coal mining activities affecting economic, social, and environmental dimensions. This condition highlights the need for a development approach that emphasizes sustainable livelihoods beyond economic growth. This community service program aims to strengthen community capacity using the Sustainable Livelihood Approach (SLA). A participatory, community-based method was applied through three stages: initial assessment, program implementation, and evaluation. The results show that social, physical, and financial capital are relatively strong, while human and natural capital remain lower, indicating structural imbalance. Community perception improved significantly from 37% positive responses in 2023 to 100% in 2024, reflecting increased trust. The Social License to Operate (SLO) index reached 77.2%, indicating strong social acceptance. The program enhanced participation, strengthened institutions, improved economic access, and promoted sustainable livelihoods. The SLA approach proved effective and replicable for empowering mining-affected rural communities.